Determining the probability of failure modes by fault tree analysis - Bujna, Marián; Lee, Chia Kuang; Prístavka, Miroslav; Nikolov, Mitko; Delikostov, Todor; Gula, Adrian (Ruse University Press, 2023)
The aim of the paper was to analyze the failure modes in the manufacturing part of the company in the production of products. To achieve this aim, we decided to use the FTA analytical methods - the fault tree method and the FMEA method. We analyzed the CNC milling machine HOLZHER 7120. We constructed a graphical representation of the fault trees for the object under study and a comprehensive fault tree. We used the FTA method to calculate the probability of occurrence of the basic events leading to the failure of the top event. The results of the FTA method served as the basis for the application of the FMEA method. We used the FMEA method to find out the causes of failures resulting from the FTA method, the probability of their occurrence, their effect, and the probability of detecting the failures. We rated the failure probability factors, the impact of failure occurrence, and the probability of detection using a numerical scale from 1 to 10 with an assigned meaning for each level. By multiplying the ratings of these factors, we obtained the overall RPN. Based on the results of the FMEA method, we determined measure suggestions for factors with RPN values greater than 30. The results of this work serve as a tool for the company to improve product quality, reduce defects, increase reliability, and influence economic results. In addition, the findings of this work are applicable to other companies, manufacturing or non-manufacturing.